Hubungan Tingkat Pengetahuan Dengan Tingkat Kecemasan Terhadap Covid-19 - Khotimah, Hus nul; Khozaimah, Putri Inni; Ulfah, Siti Qomariyah (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
Knowledge is information that is known or realized by someone in doing work. Knowledge is one of the factors that can affect anxiety. Anxiety is fear and anxiety is part of the response to stress. High anxiety can have an impact on health so that it can reduce productivity and quality of life such as decreased immunity, causing fever, flu, cough, and dizziness. Disorders are the most common group of mental disorders and have substantial functional impairment and decreased quality of life in up to 21% of patients not completing treatment, and approximately 35% receiving inadequate treatment Among those who improve, relapse occurs in more than 50% of cases in two cases. year. The purpose of this study was to determine the relationship between students' knowledge of health protocols and the anxiety of PP Nurul Jadid Paiton Probolinggo students. This research method uses the correlation method, the instrument uses a knowledge questionnaire and a Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The analysis in this research uses the Chi Square test. The results of this study indicate that there is no significant relationship between the knowledge possessed by adolescents about Covid-19 and the level of anxiety experienced by adolescents. Therefore, further researchers can re-identify what factors cause adolescent anxiety during the Covid-19 pandemic, so that it can be used as a basis in efforts to overcome adolescent mental disorders due to the pandemic.